Characteristics of fish-bone foreign bodies in the upper aero-digestive tract: The importance of identifying the species of fish. - Tadahisa Shishido (Public Library of Science (PLoS), 2021)
Background Fish bones are common foreign bodies in the upper aero-digestive tract, but their clinical features in relation to fish species have not been confirmed. We aimed to clarify the clinical characteristics of fish-bone foreign bodies and their location and removal methods depending on the fish species. Study design Retrospective, observational, monocentric study. Methods From October 2015 to May 2020, 368 patients visited the Department of Otolaryngology-Head and Neck Surgery at Tohoku University Hospital complaining of dysphagia, sore throat, or pharyngeal discomfort after eating fish. We analyzed the patients' sex and age distribution, foreign-body location, type of the fish, and the techniques used for removing the foreign body. Results Fish bones were confirmed in the upper aero-digestive tract in 270 cases (73.4%), of which 236 (87.4%) involved fish-bone foreign bodies in the mesopharynx. The most frequently involved site was the palatine tonsil (n = 170). Eel was the most frequently observed fish species (n = 39), followed by mackerel (n = 33), salmon (n = 33), horse mackerel (n = 30), and flounder (n = 30). Among the 240 cases in which the bones did not spontaneously dislocate, 109 (45.4%) were treated by endoscopic removal (103 cases) or surgery (6 cases). In pediatric cases (<12 years old), almost all fish bones were found in the mesopharynx (138/139, 99.3%), and 31 cases (22.3%) required endoscopic removal. Flounder fish bones were often lodged in the hypopharynx and esophagus (9/30, 30%), hindering spontaneous dislocation and frequently necessitating endoscopic or surgical removal (19/29, 65.5%). Conclusion The characteristics of fish-bone foreign bodies differed depending on the fish species. Flounder bones were often stuck in the hypopharynx and esophagus and were likely to require more invasive removal methods. Confirming the species of the fish could facilitate appropriate diagnosis and treatment of fish-bone foreign bodies.